(untitled) (Global Journal of Management and Business Research, 2019)
Four models of social state, modern trends in their convergence, the place of post-socialist countries in the classification of social states are consideredusing domestic and foreign scientific publications. Two general institutional models of the state, western and not-western, their genesis and essential characteristics are also described. On this basis, the manifestation of the features of various modeles in real socio-economic processes in Ukraine are analyzed. An attempt is made to determine the dominant model and to search for the vector of movement tovards an objectively determined model. The barriers caused by the manifestation of antagonistic features of complementary models are analyzed. Farther, the relationship between the models of a social state and their housing policy is examined. The contradictions in the development of the housing sector of the couuntry caused by unjustified and inconsistent steps of its reform in accordance with existing and objectively determined model are demonstrated. The necessary changes in the state housing policy of Ukraine, the prospects of future research and new housing policy conceptare determined.